Comparison of Efficacy of Intralesional Metronidazole Versus Intralesional Meglumine Antimoniate in Patients of Cutaneous Leishmaniasis - Gul, Raisa Khan; Kausar, Sameena; Naveed, Tehseen; Saleem, Sumyra; Riaz, Sarah; Said, Ghazala (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the effectiveness of intralesional Metronidazole versus intralesional Meglumine antimoniate in the treatment of cutaneous leishmaniasis. Study Design: Quasi experimental study. Place and Duration Of Study: Department of Dermatology, Combined Military Hospital, Peshawar Pakistan, from Dec 2019 to June 2020. Methodology: After informed consent from study participants and approval from the hospital ethical committee, sixty patients with cutaneous leishmaniasis from the dermatology OPD who met the inclusion criteria were chosen. Patients were randomly assigned to one of two therapy groups using simple randomization. Group A was given intralesional Metronidazole 1-2 ml (5-10mg) per lesion twice a week and Group B received intralesional Meglumine antimoniate 1-2 ml (90-180mg) per lesion twice a week for 8 weeks. Lesions were measured using a ruler and palpation to determine their size and induration. Patients were followed up till their treatment was completed. The drug was considered efficacious if there was 75 percent reduction in size or induration of lesion. Results: At the end of eight weeks, clinical effectiveness was observed in 16(53.33%) patients in Group A and 28(93.33%) patients in Group B. The results were found to be statistically significant with a p-value of 0.001. Conclusion: Intralesional Meglumine antimoniate is more effective than intralesional Metronidazole in the treatment of cutaneous leishmaniasis.